Screening of plants found in Amazonas State for lethality towards brine shrimp - Quignard, Etienne Louis Jacques (Acta Amazonica, 2020)
226 methanol and water extracts representing 74 mainly native plant species found in Amazonas State, Brazil, were tested at a standard concentration of 500 μg/mL for lethality towards larvae of the brine shrimp species Artemia franciscana. Several cytotoxic plant species were identified in this workAspidosperma marcgravianum, A. nitidum, Croton cajucara, Citrus limetta, Geissospermum argenteum, Minquartia guianensis, Piper aduncum, P. amapense, P. capitarianum, P. tuberculatum and Protium aracouchini. The results were analyzed within the context of the available traditional knowledge and uses for these plants.